Autoimmune pulmonary alveolar proteinosis and idiopathic pulmonary haemosiderosis: a dual pathology. Issue 4 (2nd April 2021) - Walsh, Laura; McCarthy, Cormac; Henry, Michael
Abstract : Pulmonary alveolar proteinosis (PAP) is a rare pulmonary condition which leads to excessive accumulation of proteinaceous material within the alveoli. Idiopathic pulmonary haemosiderosis (IPH) is another orphan lung disease and results in recurrent alveolar haemorrhage. This case study describes a case of these two rare pathologies occurring together. A man in his 50s presented with a 6-week history of haemoptysis and worsening dyspnoea. A CT scan of the thorax showed multifocal, bilateral ground glass opacification with a wide differential diagnosis. Full autoantibody screen including myositis panel and coeliac screen were negative. Bronchoscopy with bronchoalveolar lavage and tissue from a transbronchial lung cryobiopsy were non-diagnostic. Tissue from a video-assisted thoracoscopic surgery biopsy confirmed a diagnosis of PAP with IPH as a second separate pathology. The association of IPH and PAP has not previously been described. We discuss these conditions and postulate how and if they may be related.